One-Step Synthesis of Nanoliposomal Copper Diethyldithiocarbamate and Its Assessment for Cancer Therapy - Paun, Radu A; Dumut, Daciana C; Centorame, Amanda; Thuraisingam, Thusanth; Hajduch, Marian; Mistrik, Martin; Dzubak, Petr; De Sanctis, Juan B; Radzioch, Danuta; Tabrizian, Maryam (Pharmaceutics, 2022)
The metal complex copper diethyldithiocarbamate (CuET) induces cancer cell death by inhibiting protein degradation and induces proteotoxic stress, making CuET a promising cancer therapeutic. However, no clinical formulation of CuET exists to date as the drug is insoluble in water and exhibits poor bioavailability. To develop a scalable formulation, nanoliposomal (LP) CuET was synthesized using ethanol injection as a facile one-step method that is suitable for large-scale manufacturing. The nanoparticles are monodispersed, colloidally stable, and approximately 100 nm in diameter with an encapsulation efficiency of over 80%. LP-CuET demonstrates excellent stability in plasma, minimal size change, and little drug release after six-month storage at various temperatures. Additionally, melanoma cell lines exhibit significant sensitivity to LP-CuET and cellular uptake occurs predominantly through endocytosis in YUMM 1.7 cancer cells. Intracellular drug delivery is mediated by vesicle acidification with more nanoparticles being internalized by melanoma cells compared with RAW 264.7 macrophages. Additionally, the nanoparticles preferentially accumulate in YUMM 1.7 tumors where they induce cancer cell death in vivo. The development and characterization of a stable and scalable CuET formulation illustrated in this study fulfils the requirements needed for a potent clinical grade formulation.
Keywords: cancer therapeutics; drug delivery; ethanol injection; liposomes; protein corona; melanoma; copper diethyldithiocarbamate